Differential properties of Janus kinase inhibitors in the treatment of immune-mediated inflammatory diseases - Taylor, PC; Choy, E; Baraliakos, X; Szekanecz, Z; Xavier, RM; Isaacs, JD; Strengholt, S; Parmentier, JM; Lippe, R; Tanaka, Y (Oxford University Press, 2023)
Janus kinases (JAKs) are a family of cytosolic tyrosine kinases that regulate cytokine signal transduction, including cytokines involved in a range of inflammatory diseases, such as rheumatoid arthritis, psoriasis, atopic dermatitis, and inflammatory bowel disease. Several small-molecule JAK inhibitors (JAKis) are now approved for the treatment of various immune-mediated inflammatory diseases. There are, however, key differences between these agents that could potentially translate into unique clinical profiles. Each JAKi has a unique chemical structure, resulting in a distinctive mode of binding within the catalytic cleft of the target JAK, and giving rise to distinct pharmacological characteristics. In addition, the available agents have differing selectivity for JAK isoforms, as well as off-target effects against non-JAKs. Other differences include effects on haematological parameters, DNA damage repair, reproductive toxicity, and metabolism/elimination. Here we review the pharmacological profiles of the JAK inhibitors abrocitinib, baricitinib, filgotinib, peficitinib, tofacitinib, and upadacitinib.